Generating metal-organic frameworks (MOFs) from photovoltaic modules for wastewater remediation - Pham, Huu Khue (2022)
Upcycling enables the recycling efforts of E-waste to be more feasible and economically viable. Photovoltaic (PV) energy adoption has increased drastically over the years and is expected to become a mainstream energy source for the future due to its sustainability. However, waste management remains a problem as the PV panels gradually reach their end-of-life and start piling up. Many recycling strategies have been executed, but upcycling efforts to form high-value products from these PV panels are underexplored. In this paper, we report three different synthetic routes to generate metal-organic framework (MOF), MIL-53(Al) (Matériaux de l′Institut Lavoisier (MIL)), with the polymeric backsheet and aluminum that can be derived from solar panels. The synthesized MOFs have been evaluated in terms of their morphologies, thermal stability, crystallinity, and specific surface areas. Brunauer-Emmett-Teller (BET) surface areas of 1004 m2 g-1 to 1231 m2 g-1 were recorded across the synthesized MOFs. The MOFs were evaluated for their ability to adsorb commonly used harmful dyes, specifically cationic dye Methylene Blue and anionic dye Methyl Orange. The adsorption performances on MB and MO of as-synthesized MOFs were determined to be ranging from 190.1 to 262.5 mg g-1 and 244.5 to 296.7 mg g-1 respectively, demonstrating the potential of upcycling solar panels waste to valuable metal-organic framework for wastewater remediation. The findings pave the way for utilising solar panel electronic waste as a valuable resource for upcycled applications.